Drawing blood : writing architecture at the Old Slave Lodge - Lewis, Michael (School of Architecture, Planning and Geomatics, 2016)
The intent of this design dissertation was to set off on a journey of exploration and experimentation that would open itself up to unexpected or surprising results. With no expected result, this inductive process of research would hopefully result in a design investigation that was rich and original, and certainly not predetermined. In this spirit, Jeremy Till argues that research is not a linear process, and that the contingent researcher should enjoy "the sideways knocks of new ideas." These contingencies are to be seen as a field of opportunities to be gathered and filtered through the intent of the research project.' In order to document this process, a report was generated during the year that attempted track the various operations, strands of thought, and experiments that took place during the investigation. It was necessary at the time for this work to be located personally, to effectively tell the story of "my experiments with process"'. It was an interwoven mat of academic texts, narratives, personal experiences and subjective formal work, and it was hard to know at the time exactly how these would all fit together to inform a design project. Jennifer Bloomer notes that the word text comes of the past participle of the Latin texere, to weave, arguing that " ... a text is a woven thing. " In this way, the documentation of the process of initial research attempted to be a woven thing. It can be argued, however, that this research was, and still is, the design project, that the intention was not actually to inform a design project, but for the research itself to be a form of architectural and spatial projection.